Linguacultural pecularities of kazakh anthroponymy (Eurasian Journal of Philology Science and Education, 2018)
This article is devoted to the basic Kazakh anthroponymy reporting the cultural and historical life of the people, from ancient times to the present day. In the semantic relation Kazakh personal names and surnames are closely associated with traditions, beliefs, ways of life, the spiritual world of humanity. One of the peculiarities of personal names and surnames of Kazakhs is unrestricted quality in the choice of personal names. They reveal the social life, social institutions, economy, customs and traditions of the nation, the spiritual world.